Teknik Penghematan Daya Untuk Optimalisasi Voice Over Internet Protocol (VoIP) - Siti Aminah; Joko Sulistiyo (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
Power savings in wireless networks affect application quality Voice over Internet Protocol (VoIP). Power saving technique is used to measure the power used when the cellular terminal is used for VoIP. This study will explain about the effect of different techniques used to reduce power consumption at the wireless network layer on voice Quality of Service (QoS). This research will describe the jitter and delay of voice packets. The current standards for power saving techniques, at each network layer will be described, and the level of their effectiveness analyzed. In this study using WLAN to fully analyze the effect of power-saving techniques on the jitter and lag of voice packets sent. The test results are presented for description and analysis.